Beautiful birds - Hoyes, Beth (Embroidery made easy., 2022)
"Beautiful Birds (Embroidery Made Easy) teaches how to hand embroider a variety of birds using the newest embroidery trend: thread painting. Learn to create a variety of birds following the newest embroidery trend: thread painting. Through a collection of 12 detailed, full-color patterns, aspiring and established embroidery artists will discover how to employ the art of thread painting to create a range of popular birds and waterfowl from around the world, including North America, the Amazon rain forest, and Europe. Thread painting is the name for using single strands of embroidery floss to create lifelike images with beautifully blended gradients of color and detail. Fortunately, the process is not as hard as it sounds! After learning a bit about how to create gradients and blend colors, anyone can create incredible embroidered masterpieces. Beautiful Birds (Embroidery Made Easy) includes: A primer on embroidery materials, setup, and thread painting techniques; Patterns that indicate where each color should go and when the gradients should begin; For each project, step-by-step instructions and reference images of the finished piece. Perfect for needlepoint artists of all skill levels, there is no better time to learn how to create beautiful birds in embroidery"--Publisher's description.